Energy migration within hexameric hemoprotein reconstituted with Zn porphyrinoid molecules. Issue 55 (15th June 2015) - Oohora, Koji; Mashima, Tsuyoshi; Ohkubo, Kei; Fukuzumi, Shunichi; Hayashi, Takashi
Abstract : Zn porphyrinoid molecules were assembled in hexameric hemoprotein matrices to afford photosensitizer arrays to replicate a light harvesting system. Abstract : Photosensitizers, Zn protoporphyrin IX and Zn chlorin e6, are completely inserted into each heme pocket of a hexameric apohemoprotein. The fluorescence quenching efficiencies upon addition of methyl viologen are 2.3 and 2.6 fold-higher than those of the partially photosensitizer-inserted proteins, respectively, indicating that the energy migration occurs within the proteins.